Psychological stress and its relationship to assertive behavior: A field study among a sample of employees of the Syrian Trust for Development - Shams, Rama Nabil (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the relationship between psychological stress and assertive behavior among a sample of employees of Syria Trust for Development in the city of Damascus and its countryside, and to identify the differences between the mean scores of the sample members on the psychological stress scale and the affirmative behavior scale according to the variable of gender and educational level, and the study also aimed to identify the difference between the averages of high and low degrees of affirmative behavior in the face of psychological stress, the researcher chose a sample of (100) male and female employees who were chosen by random method, and the researcher used the descriptive approach. The results concluded that there is a statistically significant inverse correlation between psychological stress and affirmative behavior in the study sample, where the value of t was (-0.318) and the absence of statistically significant differences between the mean scores of the research sample on the affirmative behavior scale according to the gender variable, and the value of t was (1.881). In addition to the absence of statistically significant differences between the mean scores of the sample members on the psychological stress scale due to the gender variable, the value of t was (0.150), and there were no statistically significant differences between the mean scores of the research sample on the scale of affirmative behavior according to the educational level variable, and the value of t was ( 0.363), and there were no statistically significant differences between the mean scores of the research sample on the psychological stress scale according to the educational level variable with a value of (1.079), and finally there were statistically significant differences on the psychological stress scale according to the variable of affirmative behavior in favor of a sample of high affirmative behavior, so the value of t reached (3,690). The most important recommendations of the research were that Syria Trust for Development should develop training programs on life skills, especially the skill of affirmative behavior, in order to make the employees more able to face the psychological pressures they are exposed to, and that these trainings should be for both males and females, due to the absence of differences in the level of affirmative behavior between both genders, in addition to the fact that the administration of Syria Trust for Development offers recreational programs in managing pressures for its staff, whether male or female, because they work in the same environment, due to the difficult working conditions in light of the crisis that Syrian people are going through, and to highlight the negative role of psychological stress in the lives of individuals working in organizations through the conduct of awareness lectures, workshops and seminars, and finally the need for a psychologist in organizations to take care of the psychological affairs of employees, due to the high work pressure and its impact on the psychological state of employees and thus its reflection on performance.
Keywords: Psychological Stress; Assertive Behavior; Syria Trust for Development